PERSEPSI MAHASISWA TERHADAP IMPLEMENTASI MODEL PROBLEM POSING PADA PEMBELAJARAN MATEMATIKA BERBASIS MEDIA INTERAKTIF - Sari, Ayu Silvi Lisvian; Pramesti, Cicik; R.S., Riki Suliana; Suryanti, Suryanti (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
This study aims to determine students' perceptions of the implementation of the problem posing approach assisted by interactive media in mathematics learning, especially in shaping the professional readiness of prospective teachers. The urgency of this study is based on the importance of learning strategies that can improve critical thinking skills, creativity, and learning motivation of prospective teacher students. This study is a quantitative descriptive study involving 27 students of the mathematics education study program. Data were collected through a questionnaire consisting of ten questions grouped into three main categories, namely the problem posing aspect, interactive media, and the integration of both. The data obtained were analyzed descriptively using percentages to determine the tendency of students' perceptions of each indicator studied. The results showed that students' perceptions of the problem posing model were quite positive, with P1, P2 and P3 each scoring 77%, 86% and 87%. In the interactive media aspect, all statements (P4–P6) received very positive responses above 83%, indicating their effectiveness in facilitating understanding of concepts. The synergy between the two was also perceived very positively, with P10 recording the highest score of 98%. All items in the questionnaire were declared valid (r-count 0.381) and reliable (Cronbach's Alpha = 0.75). These findings indicate that the integration of problem posing and interactive media is effective in improving the quality of learning and shaping the professional readiness of prospective teachers. It is recommended that this approach be applied more widely in the education of prospective educators for optimal results.